Consumer Acceptance of Camel Milk in Emerging Economy. Issue 1 (1st January 2020) - Mohan, Geetha; Gupta, Vakul; Raj, Amrit; Kaur, Ramandeep
Abstract: Camel is considered as an indispensable part of desert eco-framework across the globe. Apart from helping in transport, it is also used for its milk. Camel's milk is used worldwide because of its salty taste. However, it has many beneficial effects such as cure for autism and helps to control diabetes, allergy, and also prevents liver cirrhosis. Objective of this study is to analyze the ways to make people purchase and consume camel milk. In the last few years, awareness about nutritional and medicinal benefits of camel milk has rapidly increased. Consequently, the demand of the product has also increased. Objective of this article is to analyze the consumers' willingness to buy camel milk before and after knowing its health benefits. It also explores the linkage between lifestyle diseases and consumer's willingness to buy. We analyzed data in two stages. Initially, we did qualitative analysis with twitter text mining to understand customer's sentiments about camel milk. Later, primary data was collected through structured questionnaire from a sample of 120 respondents by convenience sampling for quantitative analysis. There is a significant increase in the proportion of people willing to buy camel milk and once they were aware of the benefits, people are willing to buy more after knowing the benefits. People exposed to lifestyle diseases are more willing to buy camel milk. Hence, support of market-based awareness campaigns to stimulate demand for quality camel milk among consumers can be realized through information dissemination and awareness campaign.